Analysis of Factors Influencing Employee Compliance with Corporate Life Saving Rules (CLSR) Using the Partial Least Squares Structural Equation Modeling (PLS-SEM) Approach in the Upstream Oil and Gas Industry - Muhammad Ibnu Hidayat; Emmy Pratiwi (Journal of Social Research, 2026)
This study aimed to analyze the effects of individual, organizational, and work environment factors on employee safety compliance in the implementation of Corporate Life Saving Rules (CLSR) and to formulate strategic recommendations for improving implementation effectiveness. The study employed a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 174 workers and work partners involved in high-risk activities. The results indicated that Safety Climate, Safety Knowledge, and Safety Motivation had positive and significant effects on Safety Compliance in CLSR implementation. Safety Leadership did not directly affect Safety Compliance but played an important role in enhancing Safety Motivation, Risk Perception, and Safety Knowledge, which support safe work behavior. In addition, Workload and Work Schedule were found to have negative effects on Safety Motivation. This study concluded that improving worker compliance with CLSR requires an integrated approach involving the strengthening of safety climate, enhancement of safety knowledge, development of safety leadership, and management of work environment factors that influence workers’ motivation to engage in safe behaviors. These findings contribute theoretically to the development of safety compliance models in the upstream oil and gas industry and provide a foundation for developing strategies to improve CLSR implementation in support of achieving the Zero Fatality target.